Pengaruh Produk, Word of Mouth, Harga dan Store Atmosphere terhadap Keputusan Pembelian Konsumen pada Kafe Kesan Rantauprapat - Firman Firman; Nova Jayanti Harahap; Abd. Halim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze the effect of product, word of mouth, price and store atmosphere on consumer purchasing decisions at Kesan Rantauprapat Cafe. This research is quantitative in nature, and the research site is Kafe Kesan Rantauprapat. The data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The research population is Kesan Rantauprapat Cafe consumers in November 2022 which amounted to 563 respondents. The research sample used the Slovin formula, which was determined with a significance level of 0.1. Thus, the sample size in this study was 85 people. The results showed that the product has a positive and significant effect on purchasing decisions. Word Of Mouth Work has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Store Atmosphere has a positive and significant effect on purchasing decisions. Product, word of mouth price and store atmosphere simultaneously have a positive and significant effect on consumer purchasing decisions at Kesan Rantauprapat Cafe. Keywords: Product, Word Of Mouth, Price, Store Atmosphere, Consumer Purchasing Decisions